2020
DOI: 10.1002/bse.2714
|View full text |Cite
|
Sign up to set email alerts
|

Electoral system, corporate political donation, and carbon emission intensity: Cross‐country evidence

Abstract: We examine the association between a country's electoral system and greenhouse gas (GHG) emission intensity of firms and explore whether this association is influenced by corporate political donation. The study draws on the neo-pluralist theory of power in society to examine how possible corporate influence in the electoral systems relates to corporate environmental performance. Using a cross-country panel dataset, we find that companies operating in countries using majoritarian electoral systems (MAJ), where … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 65 publications
0
12
0
Order By: Relevance
“…The dependent variable in this study is total corporate GHG emissions calculated by aggregating Scope 1 and Scope 2 data (Bui et al, 2019; Choi & Luo, 2021; Griffin et al, 2017; Muttakin et al, 2021). Scope 1 represents direct GHG emissions which arise from sources that are owned or controlled by the reporting entity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dependent variable in this study is total corporate GHG emissions calculated by aggregating Scope 1 and Scope 2 data (Bui et al, 2019; Choi & Luo, 2021; Griffin et al, 2017; Muttakin et al, 2021). Scope 1 represents direct GHG emissions which arise from sources that are owned or controlled by the reporting entity.…”
Section: Methodsmentioning
confidence: 99%
“…Scope 2 captures indirect GHG emissions resulting from the consumption of purchased energy, including electricity, heat, cooling or steam. We use the natural logarithm of the reported amount of GHG emissions as a proxy for carbon performance of a firm (Muttakin et al, 2021).…”
Section: Dependent Variablementioning
confidence: 99%
“…The measure of majoritarianism is constructed from the World Bank's widely used Database of Political Institutions. 14 Specifically, following (Muttakin et al, 2021), we define our measure maj = 1-Proportional representation +Plurality+Housesys, where:…”
Section: Methodsmentioning
confidence: 99%
“…Ibrahim (2018) took 62 middle-income countries as samples and found that international trade and financial development played an interactive and complementary role in reducing the carbon dioxide intensity of energy use. Muttakin et al (2020) studied the relationship between national election system and enterprise greenhouse gas emission intensity and discussed whether this relationship was affected by enterprise political donations. In terms of method, some scholars analyze the driving mechanism and impact of carbon emission intensity from the perspective of spatial effect by constructing a spatial Durbin model (Xiao et al , 2019; Xue et al , 2020; Muhammad et al , 2021).…”
Section: Literature Reviewmentioning
confidence: 99%